2013
DOI: 10.1007/s00264-013-1825-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characteristics of split-depression fractures of the lateral tibial plateau (Schatzker type II): a computer-tomography–based study

Abstract: Purpose The objective of this study was to evaluate the morphological characteristics of lateral tibial plateau splitdepression fractures (Schatzker type II). Methods A retrospective analysis of radiographic and computed tomographic (CT) data of lateral tibial plateau splitdepression fractures from January 2009 to December 2010 was conducted in a level 1 trauma centre. The discontinuity arc, angle of depression centre (ADC), anterior-posterior position of articular depression centre (APDC), surface area percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
1
8

Year Published

2014
2014
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 24 publications
(23 reference statements)
2
33
1
8
Order By: Relevance
“…[18,19] Bize başvuran tibia plato kırkları da literatürle uyumlu olarak yüksek oranda Schatzker tip I ve tip II kırıklardan oluştu. [18] Tibia plato Schatzker tip I ve tip II kırıklarda posterolateral fragmanın önemli olduğunu ve cerrahi tedavide ihmal edilmemesi gerektiğini unutmamak gerekir. Uygun eklem restorasyonu ancak ameliyat öncesi iyi planlama ile mümkün olacağından hastalarda cerrahi öncesi bilgisayarlı tomografi (BT) ile değerlendirilmelidir.…”
Section: Introductionunclassified
See 3 more Smart Citations
“…[18,19] Bize başvuran tibia plato kırkları da literatürle uyumlu olarak yüksek oranda Schatzker tip I ve tip II kırıklardan oluştu. [18] Tibia plato Schatzker tip I ve tip II kırıklarda posterolateral fragmanın önemli olduğunu ve cerrahi tedavide ihmal edilmemesi gerektiğini unutmamak gerekir. Uygun eklem restorasyonu ancak ameliyat öncesi iyi planlama ile mümkün olacağından hastalarda cerrahi öncesi bilgisayarlı tomografi (BT) ile değerlendirilmelidir.…”
Section: Introductionunclassified
“…Uygun eklem restorasyonu ancak ameliyat öncesi iyi planlama ile mümkün olacağından hastalarda cerrahi öncesi bilgisayarlı tomografi (BT) ile değerlendirilmelidir. [18] Biz olgularımızın tamamında plan radyografilerle beraber BT görüntülemelerini de rutin olarak yaptık ve literatürde tanımlanan algoritma ile cerrahi tedavilerimizi gerçekleştirdik. [20,21] Brennan ve ark.…”
Section: Introductionunclassified
See 2 more Smart Citations
“…Chang et al [1] performed a CT-based measurement on eight patients and reported the average articular depression depth was 10.5 mm. Zhai et al [6] studied the fragment morphology in 71 patients and found that the posterolateral articular depression was 10.78 ± 2.05 mm, and the fractured surface area was 22.63% ± 7.85% of the total tibial plateau. Xiang et al [5] demonstrated that the posterolateral articular depression was 10.5 ± 5.2 mm (range, 2 mm to 19 mm), and the fracture fragments comprised a mean 14.3% ± 6.3% of the total articular surface (range, 8%-32%).…”
mentioning
confidence: 99%